Effect of feeding competencies on the nutritional status of children with cerebral palsy. - Campos, Maria Antónia (2007)
The purpose of this study was to determine if the feeding competencies influence the nutritional status in a group of Portuguese children with cerebral palsy (CP). One hundred and five children, aged between 4 and 12 years, were studied. Nutritional status was determined through BMI for age (BMI_y), and subescapular (SSF) and tricipital skinfolds (TSF). Feeding competencies were evaluated using the seven levels of the Functional Feeding Assessment test (FFA). This study confirmed the high prevalence of malnutrition in children with CP, since 44,8% of the sample had a BMI_y bellow the 5th percentile (Pct5). Significant differences were observed between males and females, namely in malnutrition which was higher in females (52, 4% had a BMI_y